Experimental analysis of the cyclic response of traditional timber joints and their influence on the seismic capacity of timber frame structures - Poletti, Elisa (2015)
Timber connections represent the crucial part of a timber structure and a great variability exists in terms of types of connections and mechanisms. Taking as case study the widespread traditional timber frame structures, in particular the Portuguese Pombalino buildings, one of the most common timber connection is the half-lap joint. Connections play a major role in the overall behaviour of a structure, particularly when assessing their seismic response, since damage is concentrated at the connections. For this reason, an experimental campaign was designed and distinct types of tests were carried out on traditional half-lap joints to assess their in-plane response. In particular, pull-out and in-plane cyclic tests were carried out on real scale unreinforced connections. Subsequently, the connections were retrofitted, using strengthening techniques such as self-tapping screws, steel plates and GFRP sheets. The tests chosen were meant to capture the hysteretic behaviour and dissipative capacity of the connections and characterise their response and, therefore, their influence on the seismic response of timber frame walls, particularly concerning their uplifting and rotation capacity, that could lead to rocking in the walls. In this paper, the results of the experimental campaign are presented in terms of hysteretic curves, dissipated energy and equivalent viscous damping ratio. Moreover, recommendations are provided on the most appropriate retrofitting solutions.